WADY WRODZONESurgical treatment of coarctation of the aorta in a neonate with body weight of 1200 g. Case report - Kaźmierczak, Piotr; Moll, Jadwiga A.; Moll, Jacek J. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The authors report a case of a hypotrophic infant with congenital multiorgan defects and very low body weight (1200 g) operated on for coarctation of the aorta on the 18th day of life. The case proves that operation of isthmic coarctation is an urgent but safe operation in infants with low body weight.